Evaluation of Choroidal Thickness Using Optical Coherent Tomography: A Review - Xie, Rui; Qiu, Bingjie; Chhablani, Jay; Zhang, Xinyuan (Frontiers in Medicine, 2021)
The choroid is the main source of blood and nourishment supply to the eye. The dysfunction of the choroid has been implicated in various retinal and choroidal diseases. The identification and in-depth understanding of a new entities, pachychoroid spectrum disorders are based on the tremendous progress of optical coherence tomography (OCT) technology in recent years, although visibility of choroid is challenging in the era of the Time or Spectral Domain OCT. The recent rapid revolution of OCT such as the Enhanced Depth Imaging OCT and the Swept-Source OCT has greatly contributed to the significant improvement in the analysis of the morphology and physiology of the choroid precisely, especially to the choroid-scleral boundary and vasculature. The present review highlights the recent available evidence on the measurement methodology and the clinical significance of choroidal thickness in retinal or choroidal disorders.